2013
DOI: 10.1111/ijlh.12041
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of flow cytometric T cell receptor Vβ repertoire and T cell receptor gene rearrangement in the diagnosis of large granular lymphocytic lymphoproliferation

Abstract: FC-Vβ analysis was slightly more sensitive than TCR-GR for the detection of clonal T cell lymphoproliferation. However, we must interpret the laboratory findings with clinical context as clonal T cell lymphoproliferation may occur in patients with viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…In that study, they also screened 100 unselected peripheral blood samples from newly diagnosed patients with CLL and found clonal T-cell expansion in eight patients, among whom seven patients had increased lymphocytes of large granular lymphocyte (LGL) morphology. We also noted clonal LGL proliferation in a patient with underlying unclassifi able B-cell leukemia [10]. Th e cytotoxic nature of the clonal T-cell expansions in the peripheral blood correlates with the cytotoxic nature of the PTCLs, but their role in the subsequent development of PTCL is still unclear.…”
Section: Potential Confl Ict Of Interestmentioning
confidence: 71%
“…In that study, they also screened 100 unselected peripheral blood samples from newly diagnosed patients with CLL and found clonal T-cell expansion in eight patients, among whom seven patients had increased lymphocytes of large granular lymphocyte (LGL) morphology. We also noted clonal LGL proliferation in a patient with underlying unclassifi able B-cell leukemia [10]. Th e cytotoxic nature of the clonal T-cell expansions in the peripheral blood correlates with the cytotoxic nature of the PTCLs, but their role in the subsequent development of PTCL is still unclear.…”
Section: Potential Confl Ict Of Interestmentioning
confidence: 71%
“…Flow cytometric study of the peripheral blood confirmed leukemic change with the same immunophenotype as the nodal specimen. Flow cytometric T‐cell receptor (TCR) Vβ repertoire analysis using a commercial kit (IOTest Beta Mark TCR‐Vβ Repertoire Kit; Beckman Coulter, Miami, Florida, USA) showed a non‐reactive pattern, indicating a clonal T‐cell lymphoproliferation according to our recent study …”
Section: Pathological Findingsmentioning
confidence: 78%
“…Flow cytometric T-cell receptor (TCR) Vb repertoire analysis using a commercial kit (IOTest Beta Mark TCR-Vb Repertoire Kit; Beckman Coulter, Miami, Florida, USA) showed a non-reactive pattern, indicating a clonal T-cell lymphoproliferation according to our recent study. 9 Subsequent serology study showed that the patient's serum was positive for anti-HTLV I/II antibody, which prompted us to perform Southern blotting analysis.…”
Section: Pathological Findingsmentioning
confidence: 99%
“…Flow cytometric T-cell receptor V repertoire analysis can also be used for diagnosis of a clonal T-cell population. 9,10 …”
Section: Discussionmentioning
confidence: 99%